Hydronium Ion Batteries: A Sustainable Energy Storage Solution - Zhu, Yun‐hai; Yang, Xu; Zhang, Xin‐bo (Angewandte Chemie International Edition, 2017)
Hydronium ions have been reversibly stored for the first time in an electrode of crystalline 3,4,9,10‐perylenetetracarboxylic dianhydride (PTCDA). A highly reversible discharge–charge behavior of PTCDA was observed in an aqueous acidic electrolyte of 1 m H2SO4. The capacity and the operation potentials are comparable to that of Na‐ion storage in the same electrode.